A taxonomic review of the genus Goffartia Hirschmann, 1952 (Rhabditida: Diplogastridae) with a note on the relationship of congeners - Tahseen, Qudsia; Mustaqim, Malka (Zootaxa, 2015)
This paper deals with the descriptions and diagnoses of the species of the relatively rare and poorly-understood genus Goffartia Hirschmann, 1952. A comparative account of the salient morphological characters including stoma, amphids, pharynx, and the male accessory sex organs of the six species viz., G. africana (Micoletzky, 1915) Hirschmann, 1952; G. filicaudata (Andrássy, 1968) Sudhaus & Fürst von Lieven, 2003; G. heteroceri Hirschmann, 1952; G. praepilata Shoshin, 1989 and G. variabilis (Micoletzky, 1922) Hirschmann, 1952 and the recently described G. phalacra Singh, Yousuf, Kumar & Ahmad, 2014, has been given. This paper also discusses the variations among and the relationships between these congeners, and provides an identification key.